Lithium iron phosphate positive electrode material and preparation method thereof, positive plate and preparation method thereof, and secondary battery
By using technical means such as complexed iron salts and organic polymers in the preparation process of lithium iron phosphate materials, Fe-Li anti-site defects are reduced, the lithium ion diffusion coefficient is improved, and the poor rate performance of lithium iron phosphate materials is solved. and the problem of low capacity, achieving higher battery energy density.
Patent Information
- Application Number
- CN202411313768.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-21
AI Technical Summary
When existing lithium iron phosphate materials are used in high-power electric equipment, the lithium ion diffusion coefficient is low, resulting in poor rate performance and low capacity.
Through the preparation of lithium iron phosphate materials, the chelating effect on iron ions such as complex iron salt and organic polymers and the attractive attraction of static electricity to lithium ions to prevent the priority occupying of iron, thereby reducing the Fe-li Reverse defects, increase lithium -ion diffusion coefficients.
The low Fe-li inverse defect of lithium iron phosphate material is achieved, the lithium ion diffusion coefficient is improved, and the magnification performance of the material and the energy density of the battery are improved.
Smart Images

Figure CN119340387A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a preparation method thereof, and a secondary battery. Background Art
[0002] Lithium iron phosphate with olivine structure has high theoretical capacity (170mAh / g), high working voltage, good structural stability, environmental compatibility, non-toxicity and other characteristics, making it an important positive electrode material in power and energy storage batteries. However, due to the relatively low lithium ion diffusion coefficient in lithium iron phosphate materials, its application in high-power electric devices, such as electric vehicles, which are in increasing demand. Since the diffusion of lithium ions in the lithium iron phosphate crystal structure is a one-dimensional diffusion along the
[010] plane, the lithium ion diffusion is slow. At the same time, the one-dimensional channel is easily blocked by the Fe-Li antisite defects in the crystal structure, resulting in an actual lithium ion diffusion coefficient of 10- 15 -10- 13 cm 2 / s is much lower than 10- 8 cm 2 / s theoretical value. In the early stage of lithium iron phosphate crystal formation, Fe is introduced into the crystal structure from the precursor before Li, resulting in Fe-Li antisite defects in the material. Only when the crystal structure is fully formed and all Li in the precursor is introduced into the crystal structure, can the orderly arranged lithium iron phosphate material with low defects be prepared.
[0003] Traditionally, increasing the synthesis temperature and extending the holding time can improve the integrity of the lithium iron phosphate crystal structure, but it will also cause the primary lithium iron phosphate particles to become larger, thereby hindering the diffusion of lithium ions in the material. In addition, the use of low dielectric constant solvents can also achieve lithium iron phosphate materials with low Fe-Li anti-positions, but the Fe-Li anti-position is still higher than 0.99%, resulting in low specific capacity of the synthesized lithium iron phosphate and insufficient rate performance.
[0004] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0005] One of the purposes of the present invention is to provide a lithium iron phosphate positive electrode material in view of the deficiencies in the prior art, so as to improve the problems of poor rate performance and low capacity of the current lithium iron phosphate material.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A lithium iron phosphate positive electrode material having a low Fe-Li antisite defect, wherein the mass of the Fe-Li antisite defect accounts for 0% to 2% of the total mass of the positive electrode material, and the ion diffusion coefficient of the Fe-Li antisite defect is 10 -13 ~10 -6 cm 2 / s.
[0008] The second object of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0009] Step S1, mixing a carbon source, an iron source, a phosphorus source, a lithium source and a complexing agent, and then grinding to obtain a precursor slurry;
[0010] Step S2: spray-dry the precursor slurry obtained in step S1 to obtain a dry precursor powder, and then perform heat treatment under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.
[0011] Preferably, the solid content of the precursor slurry is 30% to 60%, the D50 of the solid particles after frosting is 0.2 to 0.8 μm, and the D90 value range is 0.1 to 3 μm.
[0012] Preferably, the iron source includes complex iron salts and water-soluble iron salts; the complex iron salt includes at least one of ferrous lactate, ferric citrate, ferrous hematemesis, ferrous glycinate, ferrocene, ferrous fumarate, and ferrous gluconate.
[0013] The water-soluble iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric acetate;
[0014] The complexing agent includes at least one of 10-o-phenanthroline, EDTA, dimercaptopropanol, sodium dimercaptopropane sulfonate, mercaptoethylamine, thioglycolic acid, thiourea, ammonium fluoride, 8-hydroxyquinoline, cyanide, acetylacetone, citric acid, tartaric acid, oxalic acid, sulfosalicylic acid, triethanolamine, EGTA, ethylenediaminetetrapropionic acid, and triethylenetetramine.
[0015] The carbon source includes at least one of glucose, polyethylene glycol, sucrose, Tween, polyvinyl alcohol, polyvinyl pyrrolidone and starch; the phosphorus source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate and ammonium dihydrogen phosphate; the lithium source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium oxalate and lithium phosphide.
[0016] Preferably, in the precursor slurry of step S1, the molar ratio of Fe, P and Li is 1:(1.0-1.06):(1.0-1.1).
[0017] Preferably, step S2 is dried by spray drying equipment, the inlet temperature is controlled at 190-280°C, and the outlet temperature is controlled at 90-110°C; the heat treatment temperature in step S2 is 550-850°C, the heating rate to the heat treatment temperature is 1-5°C / min, and the heat treatment time is 5-15h.
[0018] Preferably, the inert gas in step S2 is any one of nitrogen or argon or a mixture of the two.
[0019] The third object of the present invention is to provide a positive electrode sheet comprising the positive electrode material described in any of the above paragraphs.
[0020] The fourth object of the present invention is to provide a method for preparing a positive electrode sheet, comprising the following steps: adding the above-mentioned lithium iron phosphate positive electrode material or the lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method, a conductive agent and a binder to a solvent, mixing them evenly to obtain a positive electrode active slurry, coating the positive electrode active slurry on at least one surface of the positive electrode collector, drying at 90 to 120° C. and then rolling to obtain a positive electrode sheet.
[0021] A fifth object of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: the lithium iron phosphate positive electrode material provided by the present invention has a lower Fe-Li antisite defect, so that the lithium iron phosphate not only has good electronic conductivity, but also has a very high lithium ion diffusion coefficient, which is beneficial to improving the rate performance of the material. At the same time, it has a lower Fe-Li antisite defect, so that the prepared lithium iron phosphate has a higher capacity, which is beneficial to improving the battery energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The charge and discharge curves of the lithium ion batteries of Examples 1 to 3 of the present invention and Comparative Example 1 at 0.1C / 0.1C are shown.
[0024] Figure 2 The charge and discharge curves of the lithium ion batteries of Examples 1 to 3 of the present invention and Comparative Example 1 at 0.5C / 0.5C are shown. DETAILED DESCRIPTION
[0025] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0026] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0027] In a first aspect of the present invention, a lithium iron phosphate positive electrode material is provided, which has a low Fe-Li antisite defect, wherein the mass of the Fe-Li antisite defect accounts for 0% to 2% of the total mass of the positive electrode material, and can be specifically 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, and may include but are not limited to the values listed above; the ion diffusion coefficient of the Fe-Li antisite defect is 10- 13 ~10- 6 cm 2 / s, which can be 10- 13 cm 2 / s, 10- 12 cm 2 / s, 10- 11 cm 2 / s, 10- 10 cm 2 / s, 10- 9 cm 2 / s, 10- 8 cm 2 / s, 10- 7 cm 2 / s, 10- 6 cm 2 / s, which may include but are not limited to the values listed above. As can be seen from the above, the Fe-Li antisite defect mass of the lithium iron phosphate positive electrode material accounts for 0% to 2% of the total mass of the positive electrode material, which is lower than that of the current lithium iron phosphate material. At the same time, the ion diffusion coefficient of the lithium iron phosphate material prepared by the present invention is 10- 13 ~10- 6 cm 2 / s, which is higher than the actual lithium ion diffusion coefficient of lithium iron phosphate positive electrode materials currently on the market, which is 10- 15 -10- 13 cm 2 / s; and the lithium iron phosphate material prepared by the present invention has good electrical conductivity and higher gram capacity, which is beneficial to improving the rate performance of the material and the energy density of the battery.
[0028] A second aspect of the present invention provides a method for preparing the above-mentioned lithium iron phosphate positive electrode material, comprising the following steps:
[0029] Step S1, mixing a carbon source, an iron source, a phosphorus source, a lithium source and a complexing agent, and then grinding to obtain a precursor slurry;
[0030] Step S2: spray-dry the precursor slurry obtained in step S1 to obtain a dry precursor powder, and then perform heat treatment under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.
[0031] Wherein, the solid content of the precursor slurry is 30% to 60%, specifically 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, and may include but are not limited to the above-mentioned values, preferably 40%. In some embodiments, the D50 of the frosted solid particles is 0.2 to 0.8 μm, specifically 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, and may include but are not limited to the values listed above, preferably 0.45 μm; the value range of D90 is 0.1 to 3 μm, preferably less than 2 μm.
[0032] In some embodiments, the iron source includes at least one of a complex iron salt and a water-soluble iron salt, the complex iron salt includes at least one of ferrous lactate, ferric citrate, ferrous blood salt, glycine iron, ferrocene, ferrous fumarate, and ferrous gluconate; the water-soluble iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate, and ferric acetate; the complexing agent includes at least one of 10-o-phenanthroline, EDTA, dimercaptopropanol, sodium dimercaptopropane sulfonate, mercaptoethylamine, thioglycolic acid, thiourea, ammonium fluoride, 8-hydroxyquinoline, cyanide, acetylacetone, citric acid, tartaric acid, oxalic acid, sulfosalicylic acid, triethanolamine, EGTA, ethylenediaminetetrapropionic acid, and triethylenetetramine; wherein the complex iron The salt can make the prepared lithium iron phosphate positive electrode material have low Fe-Li antisite defects. Through the chelation effect of organic polymers on iron ions and the electrostatic attraction to lithium ions, this can prevent the preferential occupation of iron in the early stage of crystal formation, thereby reducing the Fe-Li antisite defects in the subsequent heat treatment preparation process to finally obtain well-crystallized LFP nanoparticles; the carbon source includes at least one of glucose, polyethylene glycol, sucrose, Tween, polyvinyl alcohol, polyvinyl pyrrolidone and starch; the phosphorus source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate; the lithium source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium oxalate, and lithium phosphide.
[0033] Among them, in the precursor slurry described in step S1, the molar ratio of Fe, P and Li is 1:(1.0~1.06):(1.0~1.1), wherein the molar ratio of Fe, P and Li is close to 1:1:1, the ratio of the three is uniform, and the molar ratio of Li will be slightly excessive to compensate for the loss of Li element in the process of preparing lithium iron phosphate positive electrode material, thereby achieving the purpose of supplementation.
[0034] Wherein, step S2 adopts spray drying equipment for drying, and the inlet temperature is controlled at 190-280°C, specifically 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, including but not limited to the values listed above, preferably 250°C; the outlet temperature is controlled at 90-110°C, specifically 90°C, 95°C, 100°C, 105°C, 110°C, including but not limited to the values listed above, preferably 105°C; the temperature of the heat treatment in step S2 is 550-850°C, specifically The temperature is 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, and may include but are not limited to the values listed above, and is preferably 750°C; the heating rate to the heat treatment temperature is 1-5°C / min, and may specifically be 1°C, 2°C, 3°C, 4°C, 5°C, and may include but are not limited to the values listed above, and is preferably 3°C; the heat treatment time is 5-15h, and may specifically be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, and may include but are not limited to the values listed above, and is preferably 9h.
[0035] Wherein, the inert gas in step S2 is any one of nitrogen or argon or a mixture of the two.
[0036] Compared with traditional lithium iron phosphate materials, the lithium iron phosphate positive electrode material in the present application can prevent the preferential occupation of iron in the early stage of crystal formation through the chelation effect of organic polymers on iron ions and the electrostatic attraction to lithium ions, thereby reducing the Fe-Li antisite defects in the subsequent heat treatment process and finally obtaining well-crystallized LFP nanoparticles; in the early stage of LFP crystal formation, Fe is introduced into the crystal structure from the precursor preferentially than Li, thereby causing Fe-Li antisite defects in the material.
[0037] The third aspect of the present invention provides a positive electrode sheet, comprising the positive electrode material described in any of the above paragraphs, specifically comprising a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material is the lithium iron phosphate positive electrode material described in the present invention.
[0038] The positive electrode current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.
[0039] A fourth aspect of the present invention provides a method for preparing a positive electrode sheet, comprising the following steps: adding the above-mentioned lithium iron phosphate positive electrode material or the lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method, a conductive agent and a binder to a solvent, mixing them evenly to obtain a positive electrode active slurry, applying the positive electrode active slurry on at least one surface of the positive electrode collector, drying at 90 to 120°C and then rolling, the drying temperature can specifically be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, and can include but are not limited to the values listed above, preferably 105°C; obtaining a positive electrode sheet.
[0040] A fifth aspect of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.
[0041] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, copper foil.
[0042] The separator can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0043] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt can be LiPF used in high temperature electrolytes. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6 It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6 , LiTFSI; it can also be LiClO 4、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; it may also be a chain carbonate, including DFC, DMC, or EMC; it may also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and a multifunctional additive.
[0044] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0045] Example 1
[0046] The preparation method of lithium iron phosphate positive electrode material in this embodiment is:
[0047] (1) 734.8 g of ferric citrate, 115.8 g of lithium phosphate, 298.2 g of ammonium phosphate, 6 g of glucose and 10 g of EDTA were weighed to prepare a 40% solid content aqueous slurry, and then sand-milled to a D50 of 0.45 μm and a D90 of <2 μm to obtain a precursor slurry.
[0048] (2) Drying the precursor slurry obtained in step (1) in a spray drying tower, setting the spray drying inlet temperature at 250°C and the outlet temperature at 105°C, to obtain a dried precursor powder. The precursor powder obtained after spray drying is heated to 750°C at a heating rate of 3°C / min under nitrogen protection for 9 hours to obtain a lithium iron phosphate material with low Fe-Li antisite defects.
[0049] Preparation of lithium-ion battery: The lithium iron phosphate material prepared in this embodiment is mixed with deionized water in a mass ratio of 55:45 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet and the negative electrode sheet, the isolation film, are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion secondary battery.
[0050] Example 2
[0051] The preparation method of lithium iron phosphate positive electrode material in this embodiment is:
[0052] (1) 611.8 g of iron glycinate, 115.8 g of lithium phosphate, 298.2 g of ammonium phosphate, 8 g of polyethylene glycol and 5 g of citric acid were weighed to prepare a 40% solid content aqueous slurry, and then sand-milled to a D50 of 0.4 μm and a D90 of less than 2 μm to obtain a precursor slurry;
[0053] (2) Drying the precursor slurry obtained in step (1) in a spray drying tower, setting the spray drying inlet temperature at 250°C and the outlet temperature at 105°C, to obtain a dried precursor powder. The precursor powder obtained after spray drying is heated to 750°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain a lithium iron phosphate material with low Fe-Li antisite defects.
[0054] Preparation of lithium-ion battery: The lithium iron phosphate material with low Fe-Li antisite defects prepared in this embodiment is mixed with N-methylpyrrolidone in a mass ratio of 60:40 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet is wound with a negative electrode sheet and a separator to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and capacity divided to obtain a lithium-ion secondary battery.
[0055] Example 3
[0056] The preparation method of lithium iron phosphate positive electrode material in this embodiment is:
[0057] (1) Weigh 224.9 g of ferric citrate, 115.8 g of lithium dihydrogen phosphate, 6 g of sucrose, 5 g of triethanolamine and 3 g of EDTA to prepare a 40% solid content aqueous slurry, and then sand grind it to a D50 of 0.4 μm and a D90 of <2 μm to obtain a precursor slurry.
[0058] (2) Drying the precursor slurry obtained in step (1) in a spray drying tower, setting the spray drying inlet temperature at 250°C and the outlet temperature at 105°C, to obtain a dried precursor powder. The precursor powder obtained after spray drying is heated to 750°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain a lithium iron phosphate material with low Fe-Li antisite defects.
[0059] Preparation of lithium-ion battery: The lithium iron phosphate material with low Fe-Li antisite defects prepared in this embodiment is mixed with deionized water in a mass ratio of 50:30 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet is wound with a negative electrode sheet and a separator to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and divided to obtain a lithium-ion secondary battery.
[0060] Example 4
[0061] The preparation method of lithium iron phosphate positive electrode material in this embodiment is:
[0062] (1) Weigh 611.8 g of ferric glycinate, 224.9 g of ferric citrate, 115.8 g of lithium phosphate, 115.8 g of lithium dihydrogen phosphate, 298.2 g of ammonium phosphate, 8 g of polyethylene glycol, 6 g of sucrose, 5 g of triethanolamine and 5 g of citric acid to prepare a 40% solid content aqueous slurry, and then sand grind it to D50 of 0.4 μm and D90 < 2 μm to obtain a precursor slurry.
[0063] (2) Drying the precursor slurry obtained in step (1) in a spray drying tower, setting the spray drying inlet temperature at 250°C and the outlet temperature at 105°C, to obtain a dried precursor powder. The precursor powder obtained after spray drying is heated to 750°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain a lithium iron phosphate material with low Fe-Li antisite defects.
[0064] Preparation of lithium-ion battery: The lithium iron phosphate material with low Fe-Li antisite defects prepared in this embodiment is mixed with deionized water in a mass ratio of 55:45 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, it is rolled to obtain a positive electrode sheet, the prepared positive electrode sheet is wound with a negative electrode sheet and a separator to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and capacity divided to obtain a lithium-ion secondary battery.
[0065] Comparative Example 1
[0066] (1) Weigh 150.8 g of iron phosphate, 3 g of ammonium phosphate, 38.5 g of lithium carbonate, and 16 g of polyvinyl pyrrolidone to prepare a 40% solid content aqueous slurry, and then sand grind to a D50 of 0.4 μm and a D90 of <2 μm to obtain a precursor slurry.
[0067] (2) Drying the precursor slurry obtained in step (1) in a spray drying tower, setting the spray drying inlet temperature at 250°C and the outlet temperature at 105°C, to obtain a dried precursor powder. The precursor powder obtained after spray drying is heated to 750°C at a heating rate of 5°C / min under nitrogen protection for 9 hours to obtain lithium iron phosphate.
[0068] Preparation of lithium-ion battery: The lithium iron phosphate and PVDF prepared in this embodiment are dispersed in an N-methylpyrrolidone solution in a ratio of 98:2 to prepare a positive electrode slurry, the obtained positive electrode slurry is coated on an aluminum foil current collector, and after drying at 105°C, the positive electrode sheet is obtained by roller pressing, and the obtained positive electrode sheet, negative electrode sheet and isolation film are wound to obtain a battery cell, the battery cell is shelled, the electrolyte is injected into the battery shell, packaged, formed, and capacity divided to obtain a lithium-ion secondary battery.
[0069] The positive electrode materials obtained in Examples 1-3 and Comparative Example 1 were used in lithium ion button cells, and the gram capacity test was carried out at 25°C. The charge and discharge conditions were 0.1C / 0.1C and 0.5C / 0.5C, and the charge and discharge range was 2.0V-3.75V. The test results are shown in the attached Figures 1-2 .
[0070] It can be seen from the data in the figure that the battery performance used by the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention is better, indicating that the lithium iron phosphate positive electrode material prepared in the embodiment in which the preparation raw materials include complex iron salts and complexing agents has low Fe-Li antisite defects, so that the lithium iron phosphate not only has good electronic conductivity, but also has a very high lithium ion diffusion coefficient, which is beneficial to improving the rate performance of the material, and increasing the gram capacity, which is beneficial to improving the battery energy density.
[0071] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: It has a low Fe-Li antisite defect, the mass of the Fe-Li antisite defect accounts for 0% to 2% of the total mass of the positive electrode material, and the ion diffusion coefficient of the Fe-Li antisite defect is 10 -13 ~10 -6 cm 2 / s.
2. A method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The following steps are involved: Step S1, mixing a carbon source, an iron source, a phosphorus source, a lithium source and a complexing agent, and then grinding to obtain a precursor slurry; Step S2: spray-dry the precursor slurry obtained in step S1 to obtain a dry precursor powder, and then perform heat treatment under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.
3. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: The solid content of the precursor slurry is 30% to 60%, and the D50 of the solid particles after grinding is 0.2 to 0.8 μm, and the D90 is 0.1 to 3 μm.
4. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: The iron source includes at least one of a complex iron salt and a water-soluble iron salt; the complex iron salt includes at least one of ferrous lactate, ferric citrate, ferrous hematemesis, ferrous glycinate, ferrocene, ferrous fumarate, and ferrous gluconate; The water-soluble iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric acetate; The complexing agent includes at least one of 10-o-phenanthroline, EDTA, dimercaptopropanol, sodium dimercaptopropane sulfonate, mercaptoethylamine, thioglycolic acid, thiourea, ammonium fluoride, 8-hydroxyquinoline, cyanide, acetylacetone, citric acid, tartaric acid, oxalic acid, sulfosalicylic acid, triethanolamine, EGTA, ethylenediaminetetrapropionic acid, and triethylenetetramine; The carbon source comprises at least one of glucose, polyethylene glycol, sucrose, Tween, polyvinyl alcohol, polyvinyl pyrrolidone and starch; The phosphorus source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium phosphate, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate; The lithium source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium oxalate, and lithium phosphide.
5. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: In the precursor slurry of step S1, the molar ratio of Fe, P and Li is 1:(1.0-1.06):(1.0-1.1).
6. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: Step S2 adopts spray drying equipment for drying, the inlet temperature is controlled at 190-280°C, and the outlet temperature is controlled at 90-110°C; the temperature of the heat treatment in step S2 is 550-850°C, the heating rate to the heat treatment temperature is 1-5°C / min, and the heat treatment time is 5-15h.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: The inert gas in step S2 is any one of nitrogen and argon or a mixture of the two.
8. A positive electrode sheet, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 1.
9. The method for preparing a positive electrode sheet according to claim 8, characterized in that: The method comprises the following steps: adding the lithium iron phosphate positive electrode material of claim 1 or the lithium iron phosphate positive electrode material prepared by any one of the preparation methods of claims 2 to 7, a conductive agent and a binder into a solvent, mixing them evenly to obtain a positive electrode active slurry, coating the positive electrode active slurry on at least one surface of a positive electrode current collector, drying at 90 to 120° C. and then rolling to obtain a positive electrode sheet.
10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 8.
Citation Information
Cited By
Regeneration method of retired lithium iron phosphate black powder, regenerated lithium iron phosphate and secondary battery
CN122355260A
A method for regenerating retired lithium iron phosphate black powder, regenerated lithium iron phosphate, and secondary battery
CN122355260B
Lithium iron phosphate positive electrode material and preparation method therefor, positive electrode sheet, and lithium battery
WO2026188821A1